PENGARUH DESTINASI WISATA HALAL TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI NUSA TENGGARA BARAT (NTB) - DEVI ANDRI YANI; Humalia humalia (LPPM, 2022)
This study examined the effect of halal tourist destinations on economic growth in West Nusa Tenggara (NTB) Province. The analytical method used was a Multiple Linear Regression. The results indicated that the number of tourist visits positively but insignificantly influenced economic growth in NTB and hotel occupancy rate negatively but insignificantly influenced economic growth in NTB Province. Meanwhile, the results of the F test simultaneously showed that the number of tourist visits and hotel occupancy positively and significantly influenced economic growth in NTB Province. Then, the determination test result was 0.738259, which revealed that the ability of the independent variables to influence the dependent variable was 73..82%, and the other 26.18% was influenced by other variables outside of this study.Keywords: Number of Tourist Visits, Hotel Occupancy Rate, and Economic Growth.